2020
DOI: 10.1097/j.pain.0000000000002013
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor-localized cGMP-dependent protein kinase I is a critical generator for central sensitization and neuropathic pain

Abstract: Patients with neuropathic pain often experience exaggerated pain and anxiety. Central sensitization has been linked with the maintenance of neuropathic pain and may become an autonomous pain generator. Conversely, emerging evidence accumulated that central sensitization is initiated and maintained by ongoing nociceptive primary afferent inputs. However, it remains elusive what mechanisms underlie this phenomenon and which peripheral candidate contributes to central sensitization that accounts for pain hypersen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…Whole-cell patch-clamp recording was performed as described previously (79). Briefly, three weeks after viral injection of AAV-shLamb1 or AAV-scrambled shRNA into unilateral ACC, mice were anesthetized with urethane (1.2 g/kg, i.p.…”
Section: Brain Slice Patch-clamp Recordingmentioning
confidence: 99%
“…Whole-cell patch-clamp recording was performed as described previously (79). Briefly, three weeks after viral injection of AAV-shLamb1 or AAV-scrambled shRNA into unilateral ACC, mice were anesthetized with urethane (1.2 g/kg, i.p.…”
Section: Brain Slice Patch-clamp Recordingmentioning
confidence: 99%
“…Recent studies have shown that cGMP-dependent protein kinase I, a nociceptor locator, is a key pro-ducer of central sensitization and neuropathic pain [45]. We found that activation of microglia attenuated synaptic transmission and reduced neuroinflammation, synaptic function, and neuralgia.…”
Section: Research Hot Spots and Trendsmentioning
confidence: 57%
“…The latest clinical practice guidelines also point to the use of sensors and mechanical devices can help patients achieve functional movement, enhance recovery, and increase neural plasticity, as well as potential adjuncts [ 42 44 ] Central sensitization: central sensitization is a kind of hypersensitivity to pain caused by central neural plasticity, which is interwoven with psychoneuroimmunological interactions [ 34 , 35 ], and is of great significance for the diagnosis and treatment of pain. Recent studies have shown that cGMP-dependent protein kinase I, a nociceptor locator, is a key producer of central sensitization and neuropathic pain [ 45 ]. We found that activation of microglia attenuated synaptic transmission and reduced neuroinflammation, synaptic function, and neuralgia.…”
Section: Discussionmentioning
confidence: 99%
“…First, in contrast to the current study, which investigated the histone arginine methylation pattern in L4-5 spinal dorsal horn, their study focused on L4 DRG. Because a study has shown that pain-associated protein expression varies in different levels of DRG after spared nerve injury-induced neuropathic pain model [51]; and compelling evidence studies has indicated the sensory impulses of the DRG, which project onto the spinal cord, are required for neuropathic pain [52]. These evidence indicated that protein expression varies in different levels of DRG could results distinct protein changes in the center nerve system; and therefore underlies the discrepancy in CARM1 expression.…”
Section: Discussionmentioning
confidence: 99%